2018
DOI: 10.1177/0284185118780903
|View full text |Cite
|
Sign up to set email alerts
|

Combining tumor size and diffusion-weighted imaging to diagnose normal-sized metastatic pelvic lymph nodes in cervical cancers

Abstract: Background Detecting normal-sized metastatic pelvic lymph nodes (LNs) in cervical cancers, although difficult, is of vital importance. Purpose To investigate the value of diffusion-weighted-imaging (DWI), tumor size, and LN shape in predicting metastases in normal-sized pelvic LNs in cervical cancers. Material and Methods Pathology confirmed cervical cancer patients with complete magnetic resonance imaging (MRI) were documented from 2011 to 2016. A total of 121 cervical cancer patients showed small pelvic LNs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
3
20
0
1
Order By: Relevance
“…DWI has the potential to detect malignant tumors and enlarged metastatic LNs, but few studies focused on the diagnostic efficiency in detecting normal-sized metastatic LNs (11,22,23). Our study revealed that ADC mean and ADC min in enlarged metastatic LNs were significantly lower than that of benign LNs by DWI applying b values of 800 s/mm 2 (0.89 AE 0.13 Â 10 -3 mm 2 /s vs. 1.02 AE 0.13 Â 10 -3 mm 2 /s, 0.64 AE 0.15 Â 10 -3 mm 2 /s vs. 0.81 AE 0.12 Â 10 -3 mm 2 /s; P < 0.001, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…DWI has the potential to detect malignant tumors and enlarged metastatic LNs, but few studies focused on the diagnostic efficiency in detecting normal-sized metastatic LNs (11,22,23). Our study revealed that ADC mean and ADC min in enlarged metastatic LNs were significantly lower than that of benign LNs by DWI applying b values of 800 s/mm 2 (0.89 AE 0.13 Â 10 -3 mm 2 /s vs. 1.02 AE 0.13 Â 10 -3 mm 2 /s, 0.64 AE 0.15 Â 10 -3 mm 2 /s vs. 0.81 AE 0.12 Â 10 -3 mm 2 /s; P < 0.001, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor diameter is considered a good prognostic indicator of p‐LNM 6 . Several previous studies have demonstrated that MRI is the optimal imaging modality for estimating tumor diameter 10‐12 . Additionally, correlation with postoperative measurement in tumor size was higher for MRI than for pelvic examination in patients with cervical cancer 18 .…”
Section: Discussionmentioning
confidence: 99%
“…For patients with limited tumor diameter, stromal invasion, lymphovascular space invasion, parametrial involvement, or uterine corpus invasion, the rate of p‐LNM could be significantly decreased 6‐8 ; however, these parameters, except for tumor diameter, were obtained from postoperative pathological examinations. Although preoperative evaluations of lymph node status are limited, preoperative magnetic resonance imaging (MRI) could potentially be used to evaluate the risk of p‐LNM and to perform accurate and reproducible assessments of the tumor diameter 9‐12 9‐12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lymph node information in the cohort we studied was derived from biopsy or aspiration, but we could exert more clinically feasible methods to predict lymph node metastasis. Research shows that magnetic resonance imaging variables [31] and 18F-uorodeoxyglucose positron emission tomography [32] can improve the accuracy of predicting lymph node metastasis. Remarkably, degree of invasion and treatment measures had the compelling prognostic value for OS, which coincided with previous reports [33].…”
Section: Discussionmentioning
confidence: 99%